A conspicuously coloured new species of the Alpheus macrocheles group from the central Indian Ocean (Decapoda: Alpheidae) - Anker, Arthur (Zootaxa, 2023)
A new snapping shrimp species of the Alpheus macrocheles (Hailstone, 1835) group is described based on a single adult male specimen collected on an exposed forereef near Magoodhoo Island, Faafu Atoll, Maldives. Alpheus dingabadi sp. nov. is one of several species of the A. macrocheles group characterised by the presence of a stout distoventral tooth on the merus of the third pereiopod, but can be separated from all of them by several morphological features, including the unusually long appendix masculina on the second pleopod, as well as by its conspicuous and highly diagnostic colour pattern.